MEMELIHARA SPIRITUALITAS GENERASI ALFA: Pembelajaran Inovatif Guru Sekolah Minggu Berbasis Media Video - Jeujanan, Christina; Ansaka, Joane Jenie (Institut Agama Kristen Negeri Manado, 2024)
Social and technological changes affect the way Sunday school children at GKI Diaspora Doyo Baru interact with others, including in terms of religious values and spirituality. Rigid curriculum and conventional teaching methods may no longer appeal to the Alpha generation, which grew up in the digital era. Therefore, it is necessary to identify effective ways to nurture and develop the spirituality of the Alpha generation in this technological era. This study aims to create a video learning method to enhance the spirituality of the Alpha generation in the Sunday School of the GKI Diaspora Doyo Baru congregation. Qualitative approaches are used in this study, and participant observation and interviews are used to obtain data. The results showed that Sunday school teachers of the GKI Diaspora Doyo Baru congregation have paid good attention to the challenges faced by the Alpha generation. The video media designed by Sunday school teachers proved to be effective and efficient as an innovative learning tool to nurture children's faith because it provides a strong appeal. Video media can be a